1991
DOI: 10.1039/ft9918700745
|View full text |Cite
|
Sign up to set email alerts
|

Electronic charge distribution and Lewis acidity of surface aluminium atoms in γ-Al2O3: a quantum-chemical model

Abstract: A quantum-chemical cluster model has been proposed which provides an adequate description of electronic charge on differently coordinated aluminium atoms both in the bulk and on the surface of y-Al,O,.It also describes Lewis acidity of the surface aluminium atoms characterized by (a) the energy of interaction with electron donor molecules, (b) position of the local acceptor energy levels and (c) atomic charge. The model employs the semi-empirical MO CNDO/2 method in a standard parametrisation. Geometrical opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 7 publications
3
21
0
Order By: Relevance
“…Same tendency was also observed in sili-cate group, but the observed Al 2 p energies were more widely distributed than those of aluminum oxide group. These results were in good agreement with those report that in the [6] Al has smaller positive atomic charge than [4] Al 8,9 . On the other hand, a clear chemical shift was observed in aluminum hydroxide group.…”
Section: Al 2 P Peak Energysupporting
confidence: 83%
See 1 more Smart Citation
“…Same tendency was also observed in sili-cate group, but the observed Al 2 p energies were more widely distributed than those of aluminum oxide group. These results were in good agreement with those report that in the [6] Al has smaller positive atomic charge than [4] Al 8,9 . On the other hand, a clear chemical shift was observed in aluminum hydroxide group.…”
Section: Al 2 P Peak Energysupporting
confidence: 83%
“…Hughes et al 7 examined hydrous aluminas by XPS and reported that the XPS and XAES data of six coordinated aluminum ( [6] Al) were different from those of four coordinated aluminum ( [4] Al) in two dimensional chemical state plot. Fleisher et al 8 calculated atomic charges of octahedral and tetrahedral clusters in γ -Al2 O3. Then, they reported that the atomic charge of [4] Al was dominantly greater than that of [6] Al.…”
Section: Introductionmentioning
confidence: 99%
“…The large cluster size is important because second-nearest-neighbor effects have been shown to heavily influence surface chemistry in cubic aluminas [18]. Semi-empirical models have been used effectively in theoretical investigations of similar systems [8,15,19,20] and have been shown to lead to qualitative conclusions and energetic behavior consistent with first-principles calculations.…”
Section: Computational Methods and Modelsmentioning
confidence: 96%
“…Such chemisorption would produce the surface species CD 3 ␦− and D ␦+ , with the CD 3 ␦− moiety bound to a valence unsaturated Al atom of Lewis acid character. The Lewis acidity of surface Al sites on ␥-alumina has been the subject of several previous investigations [7][8][9], as has the reactivity of these sites with water [10][11][12], hydrogen sulfide [10], carbon monoxide [10], ammonia [11], pyridine [11], and methanol [13]. Previously we applied theoretical calculations to gain insight into the interaction of 1-hexene with ␥-alumina, and found the interaction to be purely repulsive at valence unsaturated surface Al sites [14].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation